2003
DOI: 10.1029/2002jd002474
|View full text |Cite
|
Sign up to set email alerts
|

A modeling study of O2 and OH airglow perturbations induced by atmospheric gravity waves

Abstract: [1] A one-dimensional model is used to investigate the relations between gravity waves and O 2 and OH airglows perturbations. The amplitude and phase of the airglow perturbations induced by gravity waves (with period > 20 min) are calculated for different vertical wavelength (10-50 km) and damping rate. The model shows that for vertically propagating gravity waves, the amplitude of airglow perturbations observed from ground is larger for longer vertical wavelength, because of the smaller cancellation effect wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
172
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(181 citation statements)
references
References 26 publications
7
172
2
Order By: Relevance
“…The negative trend indicates that when the phase difference is small, normally for a longer period of oscillation, the ratio is high, i.e., larger amplitude of variation in O 2 than that of OH. According to the model calculations of Liu and Swenson (2003) and Vargas et al (2007), the phase difference between the two emissions is a function of vertical wavelength. It is not sensitive to the period of variation (Vargas et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The negative trend indicates that when the phase difference is small, normally for a longer period of oscillation, the ratio is high, i.e., larger amplitude of variation in O 2 than that of OH. According to the model calculations of Liu and Swenson (2003) and Vargas et al (2007), the phase difference between the two emissions is a function of vertical wavelength. It is not sensitive to the period of variation (Vargas et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Recently Taori et al (2007) demonstrated the variability of wave growth rate from the OH and O 2 emission intensity temporal variations. Liu and Swenson (2003) and Vargas et al (2007) first tried to estimate the damping rate by using O 2 and OH emission intensity variations in their atmospheric models. The wave damping rate β can be defined in a term of wave amplitude:…”
Section: Wave Damping Effect In the O 2 And Oh Emission Intensity Varmentioning
confidence: 99%
See 2 more Smart Citations
“…Simultaneous wind measurements (not shown) have been used to determine the intrinsic wave period and to show that this wave was freely propagating (using the "vertical wave number squared" method described by Isler et al, 1997). Using these data an estimate of the horizontal momentum flux of this quasi-monochromatic wave can be obtained using the method described in Liu & Swenson (2003). Using an estimated BruntVaisala period of 5 min (derived from simultaneous Na lidar temperature data), the magnitude of the momentum flux was found to be 30 ± 10 m 2 /s 2 .…”
Section: Gravity Wave and Tidal Temperature Perturbationsmentioning
confidence: 99%